On the Magnetic and Thermodynamic Properties of Dark Fibrils in the Chromosphere - Matheus Kriginsky; Ramon Oliver (The Astrophysical Journal)
Fibrillar structures are ubiquitous in the solar chromosphere. An accurate determination of their properties requires the use of advanced high-resolution observations, which are now becoming broadly available from different observatories. We exploit the capabilities of multi-atom, multiline spectropolarimetric inversions using the Stockholm Inversion Code. Non–local thermodynamic equilibrium inversions of a fibril-rich area are performed using spectropolarimetric observations on the Ca ii 854.2 nm line obtained with the CRISP imaging spectropolarimeter and spectroscopic observations on the Ca ii H line obtained with the CHROMospheric Imaging Spectrometer at the Swedish 1 m Solar Telescope. Additionally, co-observations on the Mg ii h and k lines obtained with the Interface Region Imaging Spectrograph are used in the inversions to better constrain the thermodynamic properties of the fibrils. The incorporation of multiple atomic species and spectral lines proves to better constrain the properties of the plasma constituting the fibrils. In particular, the tracing of a large number of fibrils allowed for the study of the variation of the temperature and magnetic field along their projected length over the field of view. The results provide a view of fibrils possessing hot footpoints of about 5900 K. The temperature drop away from the footpoints is on average 250 K, with a larger drop of around 500 K for the longer fibrils. The magnetic field is also reported to be larger at the footpoints, being almost twice as large as the minimum value reported at the middle point of the fibrils.